Effect of the micro-texture on gear meshing noise under oil lubrication and dry friction - ZHANG Longchang; CHEN Qi; GUAN Yingchun; LI Xing; YAO Hanbo; QING Zhenhua (Jixie chuandong)
ObjectiveAt present, there is relatively little research on using micro texture methods to reduce gear meshing noise, and most of it remains at the level of computer simulation and equivalent sample testing. There is no theoretical analysis or bench testing on the noise performance of micro texture gears. It is necessary to understand the influence of micro texture on gear meshing noise under oil lubrication and dry friction conditions.MethodsA gear meshing noise calculation model was built, laser processing technology was used to manufacture micro-textured gears, a gear noise detection platform was built, and the mesh noises of micro-textured gears and non-textured gears were tested and analyzed under oil-lubricated and dry friction conditions.ResultsThe test results show that the micro-texture can help reduce gear meshing noise under both oil lubrication and dry friction conditions, at the same time, and verify the validity of the calculation model of the tooth surface meshing noise.